Methadone and neonatal abstinence syndrome (NAS): what we think we know, but do not - McCarthy, John J.; Finnegan, Loretta P. (Frontiers in Pediatrics, 2023)
Since the first use of methadone to treat OUD in pregnancy in the 1970s, there has been a long, controversial, and confusing history of studies, regulatory actions, and practice changes that have clouded an accurate perception of methadone's use in pregnancy. This review will trace this history with a focus on the effect of methadone exposure during pregnancy on neonatal abstinence syndrome (NAS). A new laboratory measure, the serum methadone/metabolite ratio (MMR), has provided a tool for documenting the profoundly dynamic nature of perinatal metabolism. Continuous induction of metabolic enzymes during pregnancy requires dose adjustments and dose frequency changes. The concept of 'fetal methadone dosing' emphasizes that relative stability of methadone levels in the fetus is an important consideration for methadone dosing in pregnancy. Finally, the effects of the societal 'war on drugs' on pediatric management of neonatal withdrawal risks will be discussed, as well as the importance of comprehensive services for mother and child including the "rooming-in" approach of neonatal care which has considerably replaced the older NICU care model of maternal/infant separation.